Clinical significance of high grade and low grade prostate intraepithelial neoplasia - M.P. Melnychuk (Medičnì Perspektivi, 2021)
Such premalignant conditions of prostate cancer (PC) as prostate intraepithelial neoplasia (PIN) are classified between benign and malignant ones. Contemporary evidence wheather PIN develops malignancy is limited and (LGPIN) data present varied results. Morphological and clinical differencies between high (HGPIN) and low grade PIN specimens in the prostate remain unclear. Aim of the work – to determine clinical significance and progression ability of high grade and low grade prostate intraepithelial neoplasia. The results of examination of 276 patients with PIN (152 patients with high grade PIN and 134 patients with low grade PIN) were assessed comparatively. During a 3 year follow-up repeated prostate biopsies were performed with 6 months interval to detect PC. Initial and repeated multifocal transrectal prostate biopsies from 12 samples were performed under transrectal ultrasonic guidance. There were statistically significant differences in PC detection rates between HGPIN and LGPIN. Patients with HGPIN had  malignization rate of 42.1% during a 3-year follow-up that was by 33.9% higher than in LGPIN patients. The spread of HGPIN lesions within prostate gland is a malignization risk factor. The mean malignization term of HGPIN is 18 months and of LGPIN – 30 months. Low and high grade PIN are gradual stages of cancerogenesis. PIN grade determines its clinical significance, while LGPIN has low malignization potential, HGPIN possesses morphological and clinical prostate characteristics similar to adenocarcinima.